2001
DOI: 10.1034/j.1399-3011.2001.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine as a potential biosynthetic precursor to the 1,5‐diazabicyclo[4:3:0]nonene residue in the efrapeptins

Abstract: Efrapeptins are a group of microheterogeneous polypeptide antibiotics produced by the fungus Tolypocladium niveum, which are potent inhibitors of mitochondrial F1-ATPase. Efrapeptins contain an unusual 1,5-diazabicyclo[4:3:0]nonene (DBN) residue at the C-terminus. This study is driven by the hypothesis that the DBN residue could, in principle, arise by oxidative cyclization of a spermidine moiety. Electrospray ionization mass spectrometry of the peptide antibiotics 'elvapeptins' from T niveum establishes the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…From this observation, the authors concluded that elvapeptins may contain a C-terminal spermidine residue that might also be converted to the amine residue of efrapeptins in vivo [50].…”
mentioning
confidence: 98%
“…From this observation, the authors concluded that elvapeptins may contain a C-terminal spermidine residue that might also be converted to the amine residue of efrapeptins in vivo [50].…”
mentioning
confidence: 98%
“…To clarify the biosynthetic relationship between efra-and elvapeptins (ELV) that have been obtained as co-metabolites from Tolypocladium inflatum IMI 202309 [49], a study was conducted which demonstrated the in vitro conversion of elvapeptins to efrapeptins by oxidative cyclization with CuCl/pyridine. From this observation, the authors concluded that elvapeptins may contain a C-terminal spermidine residue that might also be converted to the amine residue of efrapeptins in vivo [50].…”
Section: 2mentioning
confidence: 99%
“…[2] The absolute configuration of Iva as l ((S)-2-Amino-2-methylbutanoic acid) was confirmed by X-ray analysis on the basis of the relative stereochemistry the C-terminal dipeptide LeuIva.…”
Section: Introductionmentioning
confidence: 96%